Robot-assisted deep brain stimulation - Rowbottom, Hojka; Šmigoc, Tomaž; Ravnik, Janez; Flis, Vojko (Acta Medico-Biotechnica, 2024)
Deep brain stimulation (DBS) is recognised as a safe and effective treatment for several movement disorders, namely essential tremor, Parkinson’s disease, and dystonia, as well as for obsessive–compulsive disorder and refractory epilepsy. The main anatomical target of DBS is the basal ganglia. The DBS system comprises a pulse generator and surgically implanted electrodes. Lead placements must be accurate because the effects of DBS rely on the spatial restriction of the stimulation. Neurosurgical centres have started adopting robot-assisted DBS surgery. The results so far have been promising, with lead placement accuracy comparable to that of frame-based procedures. Additionally, robot-assisted procedures are shorter and less demanding on patients. Robot-assisted DBS can be used on patients who are fully awake or under general anaesthesia, as well as on children.